Answer:
D. 2x – 4 = x – 12
x = –8
Explanation:
By converting the sentence into mathematical values, we do the following:
If 4 is subtracted (- 4)
from
twice a number (2x)
the result is (=)
12 less than (- 12)
the number (x)
So is,
-4 + 2x = -12 + x
Or, organizing the elements to put "x" variable before independent number, we have
2x – 4 = x – 12
Grouping the "x" on the left side, and the independent numbers on the right side, we change the signs (+, -) when passing them from one side to the other,
2x – x = - 12 + 4
Summing algebraically (in this case subtracting by having different signs) on both sides,
2x – x = x, and
-12 + 4 = -8, then
2x – x = - 12 + 4 equals
X = - 8
Remember the rules of algebraic sum:
(1) Numbers with identical signs are added and the sign they possess is placed.
(2) Numbers with different signs are subtracted and the sign that has the largest number is placed.